Analisis Penerapan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) pada UMKM UD Rezeki Ikan Laut - Ningsih, Widya; Kadafi, Muhammad; Rahman, Abdul (Politeknik Negeri Samarinda, 2024)
This research aims to find out what records have been carried out by UMKM UD Rezeki Ikan Laut and the application of SAK EMKM to UMKM Rezeki Ikan Laut. The type of research used in this research is qualitative research. The analytical tools used are; Qualitative Analysis of Miles and Huberman (1992) and SAK EMKM. Data collection methods are; Observation, Interviews and Triangulation (Sugiyona, 2022). Rezeki Ikan Laut was founded in 2015 and has adequate business activities but has not implemented SAK EMKM. This background is interesting to research regarding the implementation of SAK EMKM. SAK EMKM consists of three components, namely: financial position report, profit and loss report, and notes to financial reports. The results of the research show that there are recordings of sales and purchases at UMKM UD Rezeki Ikan Laut but they are notyet detailed and there are still several transactions that have not been recorded. This also shows that the UD Rezeki Ikan Laut MSME has not implemented SAK EMKM.